Addressing the ethical grey zone in surgery: a framework for identification and safe introduction of novel surgical techniques and procedures. Issue 6 (11th April 2019) - Brown, Kilian; Solomon, Michael J.; Young, Jane; Seco, Michael; Bannon, Paul G.
Abstract : While the introduction of new surgical techniques can radically improve patient care, they may equally expose patients to unforeseen harms associated with untested procedures. The enthusiastic uptake of laparoscopic cholecystectomy in the early 1990s saw a dramatic increase in the rate of common bile duct injuries, and was described by Alfred Cuschieri as 'the biggest unaudited free‐for‐all in the history of surgery' due to 'a lack of effective centralised control'. Whether a new surgical intervention is considered an acceptable 'minor' variation of an established procedure, or is sufficiently 'novel' to constitute experimentation on human subjects is often unclear. Furthermore, once a new technique is identified as experimental, there is no agreed protocol for safety evaluation in a first‐in‐human setting. In phase I (first‐in‐human) pharmacological trials only small, single arm cohorts of highly selected patients are enrolled in order to establish the safety profile of a new drug. This exposes only a small number of patients to the unknown or unforeseen risks that may be associated with a new agent, in a highly regulated and scientifically rigorous manner. There is no equivalent study design for the introduction of new and experimental surgical procedures. This article proposes a practical stepwise approach to the safe introduction of new surgical procedures that surgeons and surgical departments can adopt. It includes criteria for new surgical techniques which require formal prospective ethical evaluation, and a novel study design for conducting a safety evaluation at the 'first in human' stage. Abstract : The introduction and uptake of new surgical techniques remains largely unregulated worldwide. Very few new surgical procedures are subject to rigorous safety evaluation when they are first used in humans, despite the potential for unforeseen harm to patients. This article addresses this important issue, and proposes a framework to help surgical departments and hospital administration to identify potentially harmful new techniques and presents a novel study design for introducing these techniques safely in a phase I context.